MENINGKATKAN KEMAMPUAN KANJI MELALUI MEDIA KANJI GAME ONLINE - Dyah Prasetiani (Diponegoro University, 2018)
(Title: Improving The Capabilities Of Agency Through Media Kanji Game Online) Japanese has several types of letters namely hiragana, katakana, kanji, and romaji. Each letter has its own uniqueness. For foreign learners, kanji is considered the most difficult. The results of interviews on the third semester students who followed the Kanji Shochukyu course showed that students often have difficulty in memorizing kanji, often forget the shape so that they are not able to write kanji correctly, and are often confused between read On and Kun. To overcome student difficulties in memorizing kanji, the author tries to use kanji media online game. The method used is experiment with experiment class and control class. The instrument used is postes. The result of the postes shows that the mean value of the experimental class is 82.5 while the control class is 70.1. Keywords: kanji; game online